English language skills attrition in speed and in-depth reading comprehension among EFL learners - Yu, Zhonggen; Chan, Swee Heng; Abdullah, Ain Nadzimah; Yap, Ngee Thai; Abu Samah, Bahaman (Universiti Putra Malaysia Press, 2011)
This study aimed to identify if learners experience any skills attrition in speed and in-depth reading comprehension over a two-month non-use of English language. One hundred and twenty-seven tertiary participants received both a pre-test and a post-test, whose contents were adapted from China's College English Test, Band 4 and Band 6, made up of four short passages to measure proficiency change in in-depth reading comprehension (DR) and one long passage to determine the proficiency change in speed reading comprehension (SR). The results did not indicate any statistically significant skills attrition in both modes of reading comprehension, though slight increase was found in SR, while slight skills attrition was obtained in DR. The results questioned the threshold theory in terms of subcategories and provided some possibly beneficial suggestions for English language learners.